Inhaled treatment and patient-reported outcomes in asthma - Lizano Barrantes, Catalina 1981-
The general aim of this doctoral thesis was to examine the impact on persons with persistent asthma of inhaled treatment use and sociodemographic factors, in terms of patient-reported outcomes. To achieve this, a new patient-reported tool for inhalation technique assessment was developed and validated across all ages, the Inhaler Technique Questionnaire (InTeQ); and we evaluated in pediatric population the longitudinal relationships that inhalation technique and treatment adherence present with symptom control, exacerbations, and health-related quality of life. The data used to perform this thesis came from two projects. The first one, "Assessment of the Safety of LABAs in Asthma in Routine Care by Combining Health-Care Databases and Direct Patient Follow-Up" (ASTRO-LAB), is a longitudinal asthma cohort study conducted in France and the United Kingdom in children and adults. The second project, "Asthma Research in Children and Adolescents" (ARCA), is a longitudinal, prospective, multicenter, observational study in Spain, directly derived from ASTRO-LAB to provide further evidence in children and adolescents. Our findings showed that the InTeQ is a feasible, valid, and reliable instrument for selfreporting inhalation technique in any type of device in adults and pediatric populations. Also, we confirmed longitudinal associations at within-person level of the two indicators of quality use of inhalers: for adherence to the inhaled maintenance treatment with symptom control and health-related quality of life, and for inhalation technique with health-related quality of life. It is remarkable how, although treatment adherence showed to be excellent, a third part of participants reported a suboptimal inhalation technique, supporting the need of actions for improvement in the asthma management of pediatric population.